Descriptors for Documenting Innovations and their Contributions to Impact - Sartas, Murat; Zervas, P.; Konstantinidis, S.; Sarfatti, P.; Schut, Marc; Bonaiuti, Enrico; Naziri, D.; Clarke, V. (International Potato Center, 2021)
The CGIAR Research Program on Roots, Tubers, and Bananas (RTB) has been one of the leading CGIAR research programs in designing, developing, and using complexity-sensitive tools and practices that inform innovation management decisions in CGIAR. In addition to Scaling Readiness1 , which has been adopted by One CGIAR2 , several CGIAR centers3 , and CGIAR research programs4 , RTB has developed Scaling Fund5 as an instrument to nurture the innovations that have a significant potential for Scaling. RTB has also developed many other innovations that address innovation portfolio management, such as research impact forecasts6 and gender7 . Building on its experience in developing innovation management tools and practices, RTB has recently commissioned an interdisciplinary team, the RTB Catalog Team, to develop prototypes of a novel, systematic, innovation documentation framework and an online portal featuring key innovations generated by the program since 2015. The prototypes will be essential tools for establishing a new innovation management architecture that better serves the needs of One CGIAR by systematizing the existing CGIAR digital resources such as CLARISA, MEL, MARLO, and complementing them with an application tested using the diverse innovations in the RTB portfolio. In June 2021, two milestones were completed for developing the prototypes: the Methodology that describes the conceptual model and design principles and the Review of Digital Data Resources on Innovation and Impact. This document presents the third major milestone for developing the prototypes: Descriptors for Documenting Innovations and their Contributions to Impact. Following an introduction and description of the method, this paper presents the profiles and descriptions of each of the shortlisted innovation and impact-related descriptors, selected from a longer list of 255 identified by the RTB Innovation Catalog Team from 19 global digital resources.